2018
DOI: 10.1111/nph.15002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the liverwort Marchantia polymorpha reveals that R2R3MYB activation of flavonoid production in response to abiotic stress is an ancient character in land plants

Abstract: The flavonoid pathway is hypothesized to have evolved during land colonization by plants c. 450 Myr ago for protection against abiotic stresses. In angiosperms, R2R3MYB transcription factors are key for environmental regulation of flavonoid production. However, angiosperm R2R3MYB gene families are larger than those of basal plants, and it is not known whether the regulatory system is conserved across land plants. We examined whether R2R3MYBs regulate the flavonoid pathway in liverworts, one of the earliest div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 64 publications
(114 reference statements)
4
132
0
Order By: Relevance
“…Amongst other transcription factors induced strongly were MYB14 ( Mapoly0073s0038 ), MYB6 ( Mapoly0019s0071 ) and bHLH4 ( Mapoly0028s0058 ). MYB14 activates flavonoid biosynthesis (Albert et al ., ). The function of MYB6 or bHLH4 is unknown; however, the top Arabidopsis BLAST hits for Mp bHLH4 were At MYC4 and At TT8 , which are regulators of jasmonic acid responses (Fernández‐Calvo et al ., ) and the flavonoid biosynthetic pathway, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Amongst other transcription factors induced strongly were MYB14 ( Mapoly0073s0038 ), MYB6 ( Mapoly0019s0071 ) and bHLH4 ( Mapoly0028s0058 ). MYB14 activates flavonoid biosynthesis (Albert et al ., ). The function of MYB6 or bHLH4 is unknown; however, the top Arabidopsis BLAST hits for Mp bHLH4 were At MYC4 and At TT8 , which are regulators of jasmonic acid responses (Fernández‐Calvo et al ., ) and the flavonoid biosynthetic pathway, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The function of CHIL is uncertain, but inhibition of CHIL production in angiosperms reduces flavonoid production (Morita et al ., ; Jiang et al ., ). Additionally, previously generated mutant and overexpression transgenics for Mp MYB14 (Albert et al ., ) were included in the analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Derived from the phenylpropanoid pathway, the flavonoid pathway is hypothesized to have evolved for protection against abiotic stresses by regulating the content of flavonoid (Albert et al, 2018). Flavonoids are also important bio-active compounds in medicinal plants, and they have variety of physiological effects, such as antioxidation, anti-cancer and anti-virus (Albert et al, 2018;Zhang et al, 2015).We found that the metabolic pathway of flavonoids was induced only in leaves by N-deficiency and low nitrogen. The accumulations of vitexin and xanthohumol were enhanced, by about 1.5 to 3-foldbetween low-N treatments and CK.…”
Section: Specialized Metabolic Pathway and Metabolites Analysismentioning
confidence: 85%